PHYSICOCHEMICAL CHARACTERIZATION OF LEATHER OBJECTS OF THE BYZANTINE PERIOD - PARS, ABDULKADİR; ÖZOMAY, MERAL (UNIV AGEAN, DEPT MEDITERRANEAN STUD, 2020)
Excavations carried out at the Yenikapi quarter of Istanbul under the Directorate of the Istanbul Archeological Museum between 2004-2013 and have brought the historical importance of the port to light. During the salvage excavations in Yenikapi, hundreds of leather sandals and leather objects from the Byzantine period have been uncovered. The aim of this study is to determine both tanning and coloring materials of eight leather objects belonging to the Byzantine period and physicochemical characterize the leather structure. A complementary analytical approach has been used to characterize leather objects. The ATR-FTIR analysis revealed that the leather objects were tanned with vegetable tannins (gallotanins, condensed tannins and hydrolyzable tannins). By HPLC-DAD analysis, it is known that tannin dye plants were used to color the leather (Quercus infectoria or Quercus ithaburensis). The EDS analysis result showed the possible use of cupric sulfate (CuSO4) for preliminary preparation before tanning leathers during the Byzantine period. In addition, SEM was used for visual assessment of the degree of deterioration of leathers. Based on the EDX analysis, biological deterioration factors and changes in the element ratio have shown that the leather objects deteriorate. In addition, pH, moisture content and CIE* Lab values show that there is a deterioration in the structure of leathers under the sea. The study will sheds light to leather conservation studies.
Keywords: Yenikapi; Byzantine leatherworks; ATR-FTR; HPLC-DAD; SEM-EDX; Leather conservation; POST-BYZANTINE; FTIR SPECTROSCOPY; IDENTIFICATION; DEGRADATION; TEXTILES; TANNINS; TURKEY; AGENTS